2018
DOI: 10.1002/2211-5463.12512
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA expression profile of spleen in a Clostridium perfringens type C‐induced piglet model of necrotizing enteritis

Abstract: Clostridium perfringens type C is a pathogen that causes necrotizing enteritis ( NE ), which is an intestinal tract disease in piglets. The pathogenesis of C. perfringens type C‐induced NE is still unclear, leading to a lack of effective therapies. Earlier studies have reported that circular RNA s (circ RNA s) are involved in the pathogenic processes of various diseases. However, it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 42 publications
4
11
0
Order By: Relevance
“…In pigs, Liang et al (2017) found that 21.93% of circRNAs in intergenic regions and 68.40% in exon regions through carrying out nine organs. Yan et al (2018) demonstrated that the found circRNAs consisted of approximately 74.31% exonic, 20.36% intergenic, and 5.33% intronic circRNAs in spleen, and Huang et al (2018) demonstrated that more than 86% of circRNAs consisted of exons while nearly 10% originated from intronic and intergenic regions in liver. In rats, Yang et al (2019) found that the circRNAs consisted of approximately 80.18% exonic, 0.15% intergenic, and 19.67% intronic circRNAs in pulmonary.…”
Section: Discussionmentioning
confidence: 95%
“…In pigs, Liang et al (2017) found that 21.93% of circRNAs in intergenic regions and 68.40% in exon regions through carrying out nine organs. Yan et al (2018) demonstrated that the found circRNAs consisted of approximately 74.31% exonic, 20.36% intergenic, and 5.33% intronic circRNAs in spleen, and Huang et al (2018) demonstrated that more than 86% of circRNAs consisted of exons while nearly 10% originated from intronic and intergenic regions in liver. In rats, Yang et al (2019) found that the circRNAs consisted of approximately 80.18% exonic, 0.15% intergenic, and 19.67% intronic circRNAs in pulmonary.…”
Section: Discussionmentioning
confidence: 95%
“…Echinococcus granulosus, Cryptosporidium parvum, Cryptosporidium baileyi) in animals and humans [28,33,[66][67][68][69][70][71][72][73]. The expression profiles of host circRNAs were also elucidated after infections of avian leukosis virus J [74], bovine viral diarrhea virus [75], human cytomegalovirus [76], Orf virus [30], porcine endemic diarrhea virus [29], HIV [77], transmissible gastroenteritis virus [78], Mycobacterium tuberculosis [79], Clostridium perfringens [80] and C. baileyi [33]. Furthermore, the pivotal regulatory roles of some lncRNAs (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the differentially expressed lncRNA (ALDBSSCG0000001631) involved in ileum immune response in CPID was found in porcine milk exosome. They also reported the potential lncRNA ( Yan et al, 2018a ) and circRNA ( Yan et al, 2018b ) functions in the spleen of diarrheic piglets caused by CPID. Liu et al (2018) and Chen et al (2019) revealed the potential role of lncRNA or circRNA in muscle and fat development in piglets.…”
Section: Discussionmentioning
confidence: 99%